STRUCTURED SECURITIES AND THEIR DEVELOPMENT IN LITHUANIA - Paškevičius, Arvydas; Sačilka, Ovidijus (Ekonomika, 2010)
The principal purpose of the article is to introduce structured securities, their particular features and advent into the Lithuanian financial market. The authors of the article address the premises and preconditions for the appearance of structured finance and structured securities, interpretations of related concepts and the global development trends. The system of structured securities is being designed on the basis of the principal methods of the composition of structured securities. The focus of the paper is on the group of financial instruments, including structured securities, currently designed and offered in the Lithuanian market. The article presents an analysis of the Lithuanian market in structured securities comparing it to traditional saving and investment instruments, issue volumes including the best and worst samples in terms of return rates, risks inherent to secondary securities markets and peculiarities of price calculation, also aspects of adaptation to market demands as well as the trends of its further development.